Pengaruh Brand Ambassador EXO Melalui Media Sosial Instagram terhadap Gaya Hidup Konsumtif di Kalangan Pembeli Produk Nature Republic (Studi pada Komunitas EXO-L Surabaya) - Septiani, Adist; Sumarah, Noorshanti; Norhabiba, Fitri (Universitas 17 Agustus 1945 Surabaya, 2021)
This research aimed to determine the influence of EXO's Brand Ambassador which was analyzed by using AIDDA (Attentions theory, Interest, Desire, Decision and Action)s towards the consumptive lifestyle of the buyer of Nature Republic products.This research used quantitative methods with descriptive data types. The number of samples for this study was 67 respondents. Sampling techniques used was probability sampling. Data collection technique used was an online questionnaire for the EXO-L Surabaya community.The data analysis used was a simple linear analysis using SPSS 20 program.Based on the results it showed that the influence of the variable Brand Ambassador EXO (X) In this study towards the consumptive lifestyle (Y) buyers of Nature Republic products was 31.4%. While the remaining 68.6% could be explained by other causes.Keywords: Brand Ambassador, Consumptive Lifestyle, Nature Republic, AIDDA Theory